Effectiveness of enteral ivabradine for heart rate control in septic shock: A randomised controlled trial. Issue 5 (September 2021) - Datta, Priyankar K; Rewari, Vimi; Ramachandran, Rashmi; Singh, Preet M; Ray, Bikash R; Aravindan, Ajisha; Seth, Sandeep; Parakh, Neeraj; Trikha, Anjan
Persistent tachycardia in patients with septic shock predicts poor outcome. This study sought to investigate the effect of the cardiac pacemaker current inhibitor ivabradine on heart rate and cardio-circulatory function in patients with septic shock. After informed consent, 60 patients with septic shock and persistent tachycardia (heart rate >95 /minute) were prospectively randomly assigned to receive either standard therapy for septic shock (group S) or standard therapy along with enteral ivabradine (group I) for the initial 96 hours after enrolment. Primary outcome was the difference in heart rate between the two groups during the first 96 hours. Secondary outcomes included the effect of ivabradine on haemodynamic, oxygenation, myocardial function and organ function parameters, incidence of adverse events and 30-day overall survival. Heart rate was lower in group I compared to group S (median difference in area under the curve –25.6 (95% confidence intervals –31.4 to –15.9) /minute; P <0.001). Vasopressor requirements, blood lactate levels, Sequential Organ Failure Assessment scores and E/e′ ratio were lower in group I compared to group S. Stroke volume index and ejection fraction were higher in group I while cardiac index and oxygen delivery parameters were maintained similar to group S. There was no difference in 30-day mortality or in the incidence of serious adverse events. Enteral ivabradine is effective in reducing heart rate, and improving haemodynamic parameters and cardiac function in patients with septic shock and persistent tachycardia, without increasing the incidence of adverse events.